Lightweight heavy coating material for automobile and preparation method of lightweight heavy coating material

By modifying the composite structure of silica and titanium dioxide microspheres, the rigidity and toughness of the coating are enhanced, which solves the shortcomings of existing lightweight coating materials in terms of stone impact resistance, weather resistance, high temperature resistance and corrosion resistance, and achieves multiple performance improvements of the coating.

CN120924100AActive Publication Date: 2025-11-11CHANGZHOU FU OU VEHICLE ACCESSORIES
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511450275.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-10-11
Publication Date
2025-11-11
Estimated Expiration
2045-10-11

AI Technical Summary

Technical Problem

Existing lightweight coating materials for automobiles have a poor balance in terms of stone impact resistance, weather resistance, high temperature resistance, and corrosion resistance.

Method used

A composite structure of modified silica and modified titanium dioxide microspheres is adopted. Through the design of porous hollow structure and carbon base layer, the rigidity and toughness of the coating are enhanced, and the impact resistance, weather resistance and high temperature resistance of the coating are synergistically improved. Furthermore, the corrosion resistance is improved through the light energy conversion and chemical stability of the modified titanium dioxide microspheres.

Benefits of technology

It significantly improves the coating's impact resistance, stone chip resistance, weather resistance, high temperature resistance, and corrosion resistance, thereby enhancing the overall performance of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and discloses a light-weight heavy coating material for an automobile and a preparation method of the light-weight heavy coating material. The invention discloses a light-weight heavy coating material for an automobile. Comprising the following raw materials in parts by mass: 27-29 parts of polyvinyl chloride paste resin, 3-3.5 parts of blended polyvinyl chloride resin, 22-26 parts of diisononyl phthalate, 1.5-1.7 parts of an adhesion promoter, 3-3.5 parts of a viscosity reducer, 5-5.5 parts of calcium oxide, 3-3.5 parts of modified silicon dioxide, 2-2.5 parts of zinc oxide, 17-22 parts of active nano calcium carbonate, 5-6 parts of heavy calcium carbonate, 1.5-2 parts of modified titanium dioxide microspheres and 0.8-1 part of a foaming agent. By introducing the modified silicon dioxide and modified titanium dioxide microspheres, the impact resistance, stone impact resistance, weather resistance, high temperature resistance and corrosion resistance of the light-weight heavy coating material for the automobile are effectively improved. Therefore, the method has a wider application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of coating technology, specifically relating to a lightweight recoating material for automobiles and its preparation method. Background Technology

[0002] Lightweight coating materials for automobiles are a new type of automotive coating that significantly reduces the weight per unit area of ​​the coating while ensuring that the core functions of traditional automotive coatings, such as scratch resistance and decorative properties, are not affected. Compared with traditional coatings, their core advantage lies in weight reduction without sacrificing efficiency. They avoid increasing the overall vehicle weight due to excessive coating thickness while fully meeting the rigid requirements of automobiles for coating protection and decoration. These materials are commonly found in key vehicle components such as the body, chassis, and battery packs of new energy vehicles.

[0003] However, in practical applications, lightweight coating materials for automobiles still have significant shortcomings: First, their resistance to stone impact is insufficient, especially in the chassis and lower body coatings, where they offer weak protection against road stones. Second, their high-temperature resistance is poor, easily softening and deforming under high temperatures. Third, their weather resistance and corrosion resistance are poor; after long-term exposure to sunlight and rain, the coating is prone to discoloration, pitting, and blistering. Furthermore, existing technologies often focus on optimizing single aspects of performance, making it difficult for lightweight coating materials to simultaneously possess excellent impact resistance, stone impact resistance, weather resistance, high-temperature resistance, and corrosion resistance. Therefore, the stone impact resistance, weather resistance, high-temperature resistance, and corrosion resistance of existing lightweight coating materials still need further simultaneous improvement. Summary of the Invention

[0004] To address the shortcomings mentioned in the background section, the present invention aims to provide a lightweight recoating material for automobiles and its preparation method, thereby solving the following technical problems: Existing lightweight coating materials still suffer from poor performance in balancing stone impact resistance, weather resistance, high temperature resistance, and corrosion resistance.

[0005] The objective of this invention can be achieved through the following technical solutions: A lightweight recoating material for automobiles comprises the following raw materials in parts by weight: 27-29 parts of polyvinyl chloride paste resin, 3-3.5 parts of blended polyvinyl chloride resin, 22-26 parts of diisononyl phthalate, 1.5-1.7 parts of adhesion promoter, 3-3.5 parts of viscosity reducer, 5-5.5 parts of calcium oxide, 3-3.5 parts of modified silica, 2-2.5 parts of zinc oxide, 17-22 parts of active nano-calcium carbonate, 5-6 parts of heavy calcium carbonate, 1.5-2 parts of modified titanium dioxide microspheres, and 0.8-1 parts of foaming agent; The modified silica is prepared by first grafting porous hollow silica microspheres with 3-aminopropyltriethoxysilane to form an amino transition layer, and then growing a uniform Fe-C layer by Fe-catalyzed carbon growth in a hydrogen-nitrogen-acetylene mixed atmosphere at 650-700℃ using ferrocene xylene solution as the Fe source and acetylene gas as the carbon source. The porous hollow silica microspheres are prepared by hydrolysis and condensation of tetraethyl orthosilicate and calcination in air atmosphere at 550℃, using polyacrylic acid-N,N'-methylenebisacrylamide gel as the main template and hexadecyltrimethylammonium bromide as the secondary template. The modified titanium dioxide microspheres were prepared from dicyclopentadiene, pretreated titanium dioxide, toluene-2,4-diisocyanate, dibutyltin dilaurate, tert-butyl peroxide, polyvinyl alcohol 1788, deionized water, and ethylenediamine; the pretreated titanium dioxide was octadecylamine-grafted nano-titanium dioxide.

[0006] Preferably, the modified silica is prepared by the following method: A1: Add polyacrylic acid aqueous solution to deionized water and stir well. Adjust the pH to 2.5-3.0, then heat to 60℃ and add N,N'-methylenebisacrylamide and ammonium persulfate. Stir for 30-40 min and adjust the pH to 9. Then add hexadecyltrimethylammonium bromide and stir for 30-40 min. Then add tetraethyl orthosilicate dropwise at 60℃ and stir for 12-14 h. After cooling, stir for 4-5 h. Centrifuge, wash the precipitate, freeze dry, calcine at 550℃ in air atmosphere for 5-6 h, and cool to obtain porous hollow silica microspheres. A2: Porous hollow silica microspheres were dispersed in ethanol, then 3-aminopropyltriethoxysilane was added and refluxed at 60°C for 3-4 h. After centrifugation, washing of the precipitate and vacuum drying, aminated silica was obtained. A3: Spread aminated silica evenly in a quartz boat and place it in the constant temperature zone of a tube furnace. First, heat it to 450℃ under a nitrogen atmosphere and hold it for 30-40 minutes. Then, hold it for 30-40 minutes under a mixed atmosphere of hydrogen and nitrogen. Next, heat it to 650-700℃ and inject a ferrocene xylene solution into the vaporization zone at 220℃ at the front end of the quartz tube. At the same time, introduce acetylene and hold it for 30-40 minutes. Then, turn off the acetylene and injection pump and cool it to 100-200℃. Finally, cool it under a pure nitrogen atmosphere to obtain modified silica.

[0007] Preferably, the mass ratio of deionized water, aqueous polyacrylic acid solution, N,N'-methylenebisacrylamide, ammonium persulfate, hexadecyltrimethylammonium bromide, and tetraethyl orthosilicate in A1 is 200-250:100:0.5:0.1:2:20; The mass fraction of the polyacrylic acid aqueous solution described in A1 is 10%.

[0008] Preferably, the mass ratio of the porous hollow silica microspheres, ethanol, and 3-aminopropyltriethoxysilane in A2 is 2:100-120:0.4-0.8.

[0009] Preferably, the ratio of the amount of aminated silica and the xylene solution of ferrocene in A3 is 2g: 20-30mL; The concentration of the ferrocene xylene solution described in A3 is 0.05 g / mL; In A3, the flow rate of hydrogen in the hydrogen-nitrogen mixture is 200 sccm and the flow rate of nitrogen is 300 sccm. The acetylene flow rate described in A3 is 50 sccm.

[0010] Preferably, the modified titanium dioxide microspheres are prepared as follows: B1: Add nano-titanium dioxide to anhydrous ethanol and sonicate for 1-2 hours. Then add octadecylamine and citric acid and stir and reflux at 80°C for 6-12 hours. After centrifugation, washing the precipitate and vacuum drying, pretreated titanium dioxide is obtained. B2: Add pretreated titanium dioxide to dicyclopentadiene and sonicate for 30-50 min, then add toluene-2,4-diisocyanate, dibutyltin dilaurate, and tert-butyl peroxide and stir for 10-15 min to obtain a composite oil phase; B3: Add deionized water to polyvinyl alcohol 1788 aqueous solution and stir at 45℃ for 20-30 min. Then add composite oil phase and emulsify for 10-15 min. Then sonicate for 3-5 min. Then add ethylenediamine aqueous solution dropwise and stir for 6-7 h. After cooling, centrifuge, wash precipitate and freeze dry to obtain modified titanium dioxide microspheres.

[0011] Preferably, the mass ratio of anhydrous ethanol, nano titanium dioxide, octadecylamine, and citric acid in B1 is 200-220:5:2.5:0.1.

[0012] Preferably, the mass ratio of dicyclopentadiene, pretreated titanium dioxide, toluene-2,4-diisocyanate, dibutyltin dilaurate, and tert-butyl peroxide in B2 is 100:1.5:20:0.2:0.3-0.4.

[0013] Preferably, the mass ratio of the polyvinyl alcohol 1788 aqueous solution, deionized water, composite oil phase, and ethylenediamine aqueous solution in B3 is 300:100:121.7:25-28; The mass fraction of the polyvinyl alcohol 1788 aqueous solution described in B3 is 2%; The mass fraction of the ethylenediamine aqueous solution described in B3 is 20%.

[0014] A method for preparing a lightweight recoating material for automobiles includes the following steps: Add polyvinyl chloride resin and diisononyl phthalate 1 to polyvinyl chloride paste resin and disperse at 800-1000 r / min for 8-10 min. Then, while stirring at 400-500 r / min, add adhesion promoter and viscosity reducer and stir for 3-5 min. Then, while stirring at 30-40 r / min, add calcium oxide, modified silica, zinc oxide, active nano calcium carbonate, heavy calcium carbonate, and diisononyl phthalate 2 and stir for 45-50 min. Then, add modified titanium dioxide microspheres and stir for 10-15 min. Then, roll and grind to a fineness of 15-25 μm. Finally, transfer to a reaction vessel, evacuate, add foaming agent and circulate and disperse at 600-800 r / min for 5-7 min. After vacuum standing at 70-80℃ for 24-30 h, a lightweight recoating material for automobiles is obtained. The mass ratio of diisononyl phthalate 1 to diisononyl phthalate 2 is 14-16:8-10.

[0015] The beneficial effects of this invention are: This invention provides a lightweight recoating material for automobiles and its preparation method. The invention effectively improves the impact resistance, stone chip resistance, weather resistance, high temperature resistance and corrosion resistance of the lightweight recoating material for automobiles through the following method.

[0016] (1) The porous hollow structure of the modified silica of this invention can adjust the coating density and can work synergistically with the foaming agent to enhance the lightweight effect, avoiding the loss of mechanical properties caused by simple foaming. The carbon-based composite structure formed by carbon nanotubes and iron nanoparticles on the surface of the modified silica has high rigidity and can serve as a stress dispersion point. When the coating is impacted, it can transmit the local impact stress to the surrounding matrix, avoiding the initiation of cracks caused by stress concentration. The hollow cavity can absorb energy through deformation and buffer the impact energy, reducing the direct damage of the impact to the matrix. The interface bonding force between the carbon base layer and the polyvinyl chloride matrix is ​​strong, which can avoid the defects caused by the detachment of the filler from the matrix during impact, and significantly improve the impact resistance of the coating. The rigid carbon-based composite structure can resist the cutting impact of stones and reduce surface scratches or dents. The hollow structure absorbs the impact kinetic energy of sand and gravel, reducing penetrating damage to the inside of the coating. The rigid structure of modified silica inhibits the thermo-oxidative aging shrinkage of the coating under ultraviolet light irradiation, reducing cracking caused by matrix deformation; the hollow structure reduces the thermal conductivity of the coating, weakens the synergistic aging effect of high temperature and ultraviolet light, and extends weather resistance. The high-temperature resistance of the siloxane skeleton and carbon base layer reduces heat transfer to the polyvinyl chloride matrix, and the rigid structure resists softening deformation at high temperatures, increasing the heat distortion temperature of the coating. The chemical stability of the siloxane skeleton and carbon base layer blocks the penetration of corrosive media, and the micron-sized particles fill the pores of the coating, reducing the diffusion path of corrosive media and improving the corrosion resistance of the coating.

[0017] (2) Pure nano-titanium dioxide in the modified titanium dioxide microspheres of this invention has hard and brittle properties. Direct addition can easily lead to increased coating rigidity but decreased toughness. However, the polyurethane segments in the tough shell of the modified titanium dioxide microspheres are elastic and can deform and absorb energy when impacted, thus buffering the impact stress. Polydicyclopentadiene has both rigidity and toughness, which can help disperse stress and prevent excessive deformation of the shell, thereby synergistically improving the impact resistance of the coating. The tough shell of the modified titanium dioxide microspheres can directly buffer the kinetic energy of sand and gravel impacts, reduce surface abrasive scratches, and reduce the risk of coating exposure. Its micron-sized particles can fill the tiny pores inside the coating, making the coating structure denser and reducing peeling caused by penetrating impacts of sand and gravel. The modified titanium dioxide microspheres utilize nano-titanium dioxide as the core material, which efficiently absorbs ultraviolet light and slowly releases it as heat, preventing direct damage to the molecular chains of polyvinyl chloride (PVC) by ultraviolet light. The polyurethane-polydicyclopentadiene interpenetrating network of the shell stabilizes and fixes the nano-titanium dioxide, preventing agglomeration and the creation of weather-resistant blind spots. It also reduces the oxidation failure caused by direct exposure of the nano-titanium dioxide, extending weather resistance and significantly improving the coating's weather resistance. The high melting point of the nano-titanium dioxide core material helps inhibit the high-temperature softening of PVC. The interpenetrating network of the shell maintains its toughness at high temperatures, preventing the coating from becoming brittle and reducing its mechanical properties, thus improving the material's high-temperature resistance. The modified titanium dioxide microspheres fill the tiny gaps between the resin and filler, reducing the penetration channels for corrosive media such as water, salt spray, and acid rain. The chemically stable nano-titanium dioxide core, combined with the physical barrier effect of the shell, further prevents corrosive media from contacting the metal substrate, improving corrosion resistance.

[0018] Of course, any product implementing this invention does not necessarily need to achieve all of the advantages described above at the same time. Detailed Implementation

[0019] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. The embodiments described below are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0020] Unless otherwise specified, the following information pertains to some of the raw materials used in the following embodiments and comparative examples of this invention: Polyvinyl chloride paste resin was purchased from Shanghai Chlor-Alkali Chemical Co., Ltd., grade: P450; blended polyvinyl chloride resin was purchased from Shanghai Chlor-Alkali Chemical Co., Ltd., grade: SB100; polyvinyl alcohol 1788 was purchased from Hubei Yongkuo Technology Co., Ltd., product number: YK2833; polyacrylic acid was purchased from Hubei Junrui Biotechnology Co., Ltd., product number: JR1196; adhesion promoter was purchased from Wuxi Shengyi Synthetic Materials Co., Ltd., grade: SY-533; viscosity reducer was purchased from Jingmen Petrochemical, grade: D80; foaming agent was purchased from Beijing Senchang Taihe Technology Co., Ltd., grade: F-78D.

[0021] Example 1: A method for preparing a lightweight recoating material for automobiles is as follows: S1: Add 100g of 10% polyacrylic acid aqueous solution to 200g deionized water and stir at 300r / min for 30min. Adjust the pH to 2.5 with 10% hydrochloric acid and heat to 60℃. Add 0.5g N,N'-methylenebisacrylamide and 0.1g ammonium persulfate and stir for 30min. Adjust the pH to 9.0 with 28% ammonia and stir for 8min. Then add 2g hexadecyltrimethylammonium bromide and stir for 30min. Then add 20g tetraethyl orthosilicate dropwise at 1mL / min at 60℃ and stir for 12h. After cooling to 25℃, stir for 4h. Then centrifuge and wash the precipitate 5 times with deionized water. Freeze-dry under vacuum at -50℃ and 10Pa for 24h. Then heat to 550℃ at 2℃ / min and calcine at 550℃ in air atmosphere for 5h. After cooling, porous hollow silica microspheres are obtained. S2: 2g of porous hollow silica microspheres were dispersed in 100g of ethanol, then 0.4g of 3-aminopropyltriethoxysilane was added and refluxed at 60℃ for 3h. The mixture was then centrifuged and the precipitate was washed three times with anhydrous ethanol. The precipitate was then vacuum dried at 55℃ for 12h to obtain aminated silica. S3: Spread 2g of aminated silica in a quartz boat and place it in the constant temperature zone of a tube furnace. First, heat it to 450℃ at 10℃ / min in a nitrogen atmosphere and hold it for 30min. Then, hold it for 30min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Next, heat it to 650℃ at 10℃ / min and inject 20mL of xylene solution with a concentration of 0.05g / mL of ferrocene at 0.5mL / min into the 220℃ vaporization zone at the front end of the quartz tube. At the same time, introduce acetylene at a flow rate of 50sccm and hold it for 30min. Then, turn off the acetylene and injection pump and cool it to 100℃ at 5℃ / min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Finally, switch to a pure nitrogen atmosphere and cool it to 30℃ to obtain modified silica. S4: Add 5g of nano-titanium dioxide to 200g of anhydrous ethanol and ultrasonically disperse for 1h. Then add 2.5g of octadecylamine and 0.1g of citric acid and stir and reflux at 80℃ for 6h. Centrifuge and wash the precipitate three times with anhydrous ethanol. Then vacuum dry at 80℃ for 12h to obtain pretreated titanium dioxide. S5: Add 1.5g of pretreated titanium dioxide to 100g of dicyclopentadiene and sonicate for 30min. Then add 20g of toluene-2,4-diisocyanate, 0.2g of dibutyltin dilaurate, and 0.3g of tert-butyl peroxide and stir for 10min to obtain a composite oil phase. S6: Add 100g of deionized water to 300g of 2% polyvinyl alcohol 1788 aqueous solution and stir at 400r / min for 20min at 45℃. Then add 121.7g of composite oil phase and emulsify at 1000r / min for 10min. Then sonicate for 3min. Then add 25g of 20% ethylenediamine aqueous solution dropwise at 1.2mL / min and stir at 400r / min for 6h at 45℃. After cooling, centrifuge and wash the precipitate three times with deionized water. Finally, freeze dry under vacuum at -50℃ and 10Pa for 24h to obtain modified titanium dioxide microspheres. S7: Add 3g of blended polyvinyl chloride resin and 14g of diisononyl phthalate to 27g of polyvinyl chloride paste resin and disperse at 800r / min for 8min. Then, while stirring at 400r / min, add 1.5g of adhesion promoter and 3g of viscosity reducer and stir for 3min. Then, while stirring at 30r / min, add 5g of calcium oxide, 3g of modified silica, 2g of zinc oxide, 17g of active nano calcium carbonate, 5g of heavy calcium carbonate, and 8g of diisononyl phthalate and stir for 45min. Then, add 1.5g of modified titanium dioxide microspheres and stir for 10min. Then, roll-mill to a fineness of 15μm. Finally, transfer to a reaction vessel, evacuate, add 0.8g of foaming agent and circulate and disperse at 600r / min for 5min. After standing under vacuum at 70℃ for 24h, a lightweight recoating material for automobiles is obtained.

[0022] Example 2: A method for preparing a lightweight recoating material for automobiles is as follows: S1: Add 100g of 10% polyacrylic acid aqueous solution to 225g deionized water and stir at 300r / min for 40min. Adjust the pH to 2.8 with 10% hydrochloric acid and heat to 60℃. Add 0.5g N,N'-methylenebisacrylamide and 0.1g ammonium persulfate and stir for 35min. Adjust the pH to 9 with 28% ammonia and stir for 9min. Then add 2g hexadecyltrimethylammonium bromide and stir for 35min. Then add 20g tetraethyl orthosilicate dropwise at 1mL / min at 60℃ and stir for 13h. After cooling to 28℃, stir for 4.5h. Then centrifuge and wash the precipitate 6 times with deionized water. Freeze-dry under vacuum at -50℃ and 10Pa for 25h. Then heat to 550℃ at 2℃ / min and calcine at 550℃ in air atmosphere for 5.5h. After cooling, porous hollow silica microspheres are obtained. S2: 2g of porous hollow silica microspheres were dispersed in 110g of ethanol, then 0.6g of 3-aminopropyltriethoxysilane was added and refluxed at 60℃ for 3.5h. The mixture was then centrifuged and the precipitate was washed four times with anhydrous ethanol and dried under vacuum at 55℃ for 13.5h to obtain aminated silica. S3: Spread 2g of aminated silica in a quartz boat and place it in the constant temperature zone of a tube furnace. First, heat it to 450℃ at 10℃ / min in a nitrogen atmosphere and hold it for 35min. Then, hold it for 35min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Next, heat it to 680℃ at 10℃ / min and inject 25mL of xylene solution with a concentration of 0.05g / mL of ferrocene at 0.5mL / min into the 220℃ vaporization zone at the front end of the quartz tube. At the same time, introduce acetylene at a flow rate of 50sccm and hold it for 35min. Then, turn off the acetylene and injection pump and cool it to 150℃ at 5℃ / min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Finally, switch to a pure nitrogen atmosphere and cool it to 35℃ to obtain modified silica. S4: Add 5g of nano-titanium dioxide to 210g of anhydrous ethanol and ultrasonically disperse for 1.5h. Then add 2.5g of octadecylamine and 0.1g of citric acid and stir and reflux at 80℃ for 9h. After centrifugation and washing the precipitate 4 times with anhydrous ethanol, vacuum dry at 80℃ for 14h to obtain pretreated titanium dioxide. S5: Add 1.5g of pretreated titanium dioxide to 100g of dicyclopentadiene and sonicate for 40min. Then add 20g of toluene-2,4-diisocyanate, 0.2g of dibutyltin dilaurate, and 0.35g of tert-butyl peroxide and stir for 13min to obtain the composite oil phase. S6: 100g of deionized water was added to 300g of a 2% (w / w) polyvinyl alcohol 1788 aqueous solution and stirred at 400r / min for 25min at 45℃. Then, 121.7g of composite oil phase was added and emulsified at 1300r / min for 13min. The mixture was then sonicated for 4min. Next, 26.5g of a 20% (w / w) ethylenediamine aqueous solution was added dropwise at 1.2mL / min and stirred at 400r / min for 6.5h at 45℃. After cooling, the mixture was centrifuged and the precipitate was washed four times with deionized water. Finally, the mixture was freeze-dried under vacuum at -50℃ and 10Pa for 25h to obtain modified titanium dioxide microspheres. S7: Add 3.3g of blended polyvinyl chloride resin and 15g of diisononyl phthalate to 28g of polyvinyl chloride paste resin and disperse at 900r / min for 9min. Then, while stirring at 450r / min, add 1.6g of adhesion promoter and 3.3g of viscosity reducer and stir for 4min. Then, while stirring at 35r / min, add 5.3g of calcium oxide, 3.2g of modified silica, 2.3g of zinc oxide, 20g of active nano calcium carbonate, 5.5g of heavy calcium carbonate, and 9g of diisononyl phthalate and stir for 48min. Then, add 1.8g of modified titanium dioxide microspheres and stir for 13min. Then, roll-mill to a fineness of 20μm. Finally, transfer to a reaction vessel, evacuate, add 0.9g of foaming agent and circulate and disperse at 700r / min for 6min. After standing under vacuum at 75℃ for 27h, a lightweight recoating material for automobiles is obtained.

[0023] Example 3: A method for preparing a lightweight recoating material for automobiles is as follows: S1: Add 100g of 10% polyacrylic acid aqueous solution to 250g deionized water and stir at 300r / min for 50min. Adjust the pH to 3 with 10% hydrochloric acid and heat to 60℃. Add 0.5g N,N'-methylenebisacrylamide and 0.1g ammonium persulfate and stir for 40min. Adjust the pH to 9 with 28% ammonia and stir for 10min. Then add 2g hexadecyltrimethylammonium bromide and stir for 40min. Then add 20g tetraethyl orthosilicate dropwise at 1mL / min at 60℃ and stir for 14h. After cooling to 30℃, stir for 5h. Then centrifuge and wash the precipitate 7 times with deionized water. Freeze-dry under vacuum at -50℃ and 10Pa for 26h. Then heat to 550℃ at 2℃ / min and calcine at 550℃ in air atmosphere for 6h. After cooling, porous hollow silica microspheres are obtained. S2: 2g of porous hollow silica microspheres were dispersed in 120g of ethanol, then 0.8g of 3-aminopropyltriethoxysilane was added and refluxed at 60℃ for 4h. The mixture was then centrifuged and the precipitate was washed 5 times with anhydrous ethanol and dried under vacuum at 55℃ for 15h to obtain aminated silica. S3: Spread 2g of aminated silica in a quartz boat and place it in the constant temperature zone of a tube furnace. First, heat it to 450℃ at 10℃ / min in a nitrogen atmosphere and hold it for 40min. Then, hold it for 40min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Next, heat it to 700℃ at 10℃ / min and inject 30mL of xylene solution with a concentration of 0.05g / mL ferrocene at 0.5mL / min into the 220℃ vaporization zone at the front end of the quartz tube. At the same time, introduce acetylene at a flow rate of 50sccm and hold it for 40min. Then, turn off the acetylene and injection pump and cool it to 200℃ at 5℃ / min in a mixed gas atmosphere of 200sccm hydrogen and 300sccm nitrogen. Finally, switch to a pure nitrogen atmosphere and cool it to 40℃ to obtain modified silica. S4: Add 5g of nano-titanium dioxide to 220g of anhydrous ethanol and ultrasonically disperse for 2h. Then add 2.5g of octadecylamine and 0.1g of citric acid and stir and reflux at 80℃ for 12h. After centrifugation and washing the precipitate 5 times with anhydrous ethanol, vacuum dry at 80℃ for 15h to obtain pretreated titanium dioxide. S5: Add 1.5g of pretreated titanium dioxide to 100g of dicyclopentadiene and sonicate for 50min. Then add 20g of toluene-2,4-diisocyanate, 0.2g of dibutyltin dilaurate, and 0.4g of tert-butyl peroxide and stir for 15min to obtain the composite oil phase. S6: 100g of deionized water was added to 300g of 2% polyvinyl alcohol 1788 aqueous solution and stirred at 400r / min for 30min at 45℃. Then, 121.7g of composite oil phase was added and emulsified at 1500r / min for 15min. After ultrasonic treatment for 5min, 28g of 20% ethylenediamine aqueous solution was added dropwise at 1.2mL / min and stirred at 400r / min for 7h at 45℃. After cooling, the mixture was centrifuged and the precipitate was washed 5 times with deionized water. Finally, the mixture was freeze-dried under vacuum at -50℃ and 10Pa for 26h to obtain modified titanium dioxide microspheres. S7: Add 3.5g of blended PVC resin and 16g of diisononyl phthalate to 29g of PVC paste resin and disperse at 1000r / min for 10min. Then, while stirring at 500r / min, add 1.7g of adhesion promoter and 3.5g of viscosity reducer and stir for 5min. Then, while stirring at 40r / min, add 5.5g of calcium oxide, 3.5g of modified silica, 2.5g of zinc oxide, 22g of active nano calcium carbonate, 6g of heavy calcium carbonate, and 10g of diisononyl phthalate and stir for 50min. Then, add 2g of modified titanium dioxide microspheres and stir for 15min. Then, roll-mill to a fineness of 25μm. Finally, transfer to a reaction vessel, evacuate, add 1g of foaming agent and circulate and disperse at 800r / min for 7min. After standing under vacuum at 80℃ for 30h, a lightweight recoating material for automobiles is obtained.

[0024] Comparative Example 1: Compared with Example 1, this comparative example only replaces the "modified silica" added in the preparation process of S7 with the "aminated silica" prepared in S2. All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a lightweight recoating material for automobiles is obtained.

[0025] Comparative Example 2: Compared with Example 1, this comparative example only did not add "modified silica" in the preparation process of S7. All other steps and parameters were the same, and will not be repeated here. The final result was a lightweight recoating material for automobiles.

[0026] Comparative Example 3: Compared with Example 1, this comparative example only replaces the "modified titanium dioxide microspheres" added in the preparation process of S7 with the "pretreated titanium dioxide" prepared in S4. All other steps and parameters are the same, and will not be repeated in this comparative example. Finally, a lightweight heavy coating material for automobiles is obtained.

[0027] Comparative Example 4: Compared with Example 1, this comparative example only omits the addition of "modified titanium dioxide microspheres" in the preparation process of S7. All other steps and parameters are the same, and will not be repeated here. The final result is a lightweight recoating material for automobiles.

[0028] Performance testing: Lightweight recoating material for automobiles was sprayed onto a 150×70mm×0.3mm tinplate that had been sanded (400 grit) and cleaned and dried. The coating was applied in two coats (pre-baking at 60℃ for 30 minutes after the first coat) with a thickness of 40μm for each coat, resulting in a test sample with a total dry film thickness of 80μm.

[0029] Impact resistance testing: Referring to GB / T 1732-2020 "Test Method for Impact Resistance of Coating Films", a 1kg hammer at a height of 1m above the test specimen was used to determine the impact strength (kJ / m²) of the surface coating of the test specimens made of the lightweight recoating materials for automobiles prepared in Examples 1-3 and Comparative Examples 1-4 of this invention. 2 The test results are shown in Table 1.

[0030] Determination of stone impact resistance: The test plate was clamped directly onto the test plate fixture. 1000g of pebbles (9.5-16.5mm in diameter) were loaded into the hopper of the stone impact tester. The air pressure was adjusted to 0.5MPa, and then the air valve was opened. After all the pebbles were shot, the pebbles were reloaded, and the impact was repeated for a total of 25 impacts. The air valve was then closed. The test plate was removed, and the entire stone impact surface was covered with tape. The tape was then quickly peeled off by hand, and the coating surface was observed for peeling or cracks. The stone impact resistance of the surface coating of the test sample made of the lightweight heavy coating material for automobiles prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was determined according to the above method. The test results are shown in Table 1.

[0031] Weather resistance testing: Referring to GB / T 1766-2008 "Rating Method for Aging of Paint and Varnish Coatings", the coating experience of the test samples made of the lightweight recoating materials for automobiles prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was determined to be 0.76 W / m. 2 The color difference ΔE before and after 1000h of cyclic UV aging at 340nm was used to reflect the weather resistance of the coating. The test results are shown in Table 1.

[0032] Determination of high temperature resistance: Referring to GB / T 1634.2-2019 "Determination of Deformation Temperature of Plastics under Load - Part 2: Plastics and Hard Rubber", the heat distortion temperature (°C) of the coatings of the test specimens made of the lightweight recoating materials for automobiles prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was determined under a load of 1.8 MPa. The test results are shown in Table 1.

[0033] Corrosion resistance testing: Referring to GB / T 10125-2021 "Artificial Atmosphere Corrosion Test - Salt Spray Test" standard, the test samples were sealed with epoxy putty, then placed in a salt spray test chamber. A 24-hour salt spray and 24-hour drying cycle test was conducted at 35℃ using a 5% sodium chloride solution with pH=7. Samples were taken every 48 hours for observation, and the test duration for pitting and blistering on the surface of each sample was recorded. The neutral salt spray test ended when the last sample showed pitting and blistering. The corrosion resistance (h) of the surface coating of the test samples made from the lightweight heavy-duty automotive coating materials prepared in Examples 1-3 and Comparative Examples 1-4 of this invention was determined according to the above method. The test results are shown in Table 1.

[0034] Table 1: Performance test results of Examples 1-3 and Comparative Examples 1-4

[0035] Data Analysis: As can be seen from Table 1, the lightweight recoating material for automobiles prepared in the embodiments of the present invention has excellent impact resistance, stone chip resistance, weather resistance, high temperature resistance and corrosion resistance.

[0036] In the description of this specification, references to terms such as "an embodiment," "example," "specific example," etc., indicate that a specific feature, structure, material, or characteristic described in connection with that embodiment or example is included in at least one embodiment or example of the invention. In this specification, illustrative expressions of the above terms do not necessarily refer to the same embodiment or example. Furthermore, the specific features, structures, materials, or characteristics described may be combined in any suitable manner in one or more embodiments or examples.

[0037] The foregoing has shown and described the basic principles, main features, and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The embodiments and descriptions in the specification are merely illustrative of the principles of the invention. Various changes and modifications can be made to the invention without departing from its spirit and scope, and all such changes and modifications fall within the scope of the claimed invention.

Claims

1. A lightweight recoating material for automobiles, characterized in that, The raw materials include the following parts by weight: 27-29 parts of polyvinyl chloride paste resin, 3-3.5 parts of blended polyvinyl chloride resin, 22-26 parts of diisononyl phthalate, 1.5-1.7 parts of adhesion promoter, 3-3.5 parts of viscosity reducer, 5-5.5 parts of calcium oxide, 3-3.5 parts of modified silica, 2-2.5 parts of zinc oxide, 17-22 parts of active nano calcium carbonate, 5-6 parts of heavy calcium carbonate, 1.5-2 parts of modified titanium dioxide microspheres, and 0.8-1 parts of foaming agent; The modified silica is prepared by first grafting porous hollow silica microspheres with 3-aminopropyltriethoxysilane to form an amino transition layer, and then growing a uniform Fe-C layer by Fe-catalyzed carbon growth in a hydrogen-nitrogen-acetylene mixed atmosphere at 650-700℃ using ferrocene xylene solution as the Fe source and acetylene gas as the carbon source. The porous hollow silica microspheres are prepared by hydrolysis and condensation of tetraethyl orthosilicate and calcination in air atmosphere at 550℃, using polyacrylic acid-N,N'-methylenebisacrylamide gel as the main template and hexadecyltrimethylammonium bromide as the secondary template. The modified titanium dioxide microspheres were prepared from dicyclopentadiene, pretreated titanium dioxide, toluene-2,4-diisocyanate, dibutyltin dilaurate, tert-butyl peroxide, polyvinyl alcohol 1788, deionized water, and ethylenediamine; the pretreated titanium dioxide was octadecylamine-grafted nano-titanium dioxide.

2. The lightweight recoating material for automobiles according to claim 1, characterized in that, The modified silica is prepared as follows: A1: Add polyacrylic acid aqueous solution to deionized water and stir well. Adjust the pH to 2.5-3.0, then heat to 60℃ and add N,N'-methylenebisacrylamide and ammonium persulfate. Stir for 30-40 min and adjust the pH to 9. Then add hexadecyltrimethylammonium bromide and stir for 30-40 min. Then add tetraethyl orthosilicate dropwise at 60℃ and stir for 12-14 h. After cooling, stir for 4-5 h. Centrifuge, wash the precipitate, freeze dry, calcine at 550℃ in air atmosphere for 5-6 h, and cool to obtain porous hollow silica microspheres. A2: Porous hollow silica microspheres were dispersed in ethanol, then 3-aminopropyltriethoxysilane was added and refluxed at 60°C for 3-4 h. After centrifugation, washing of the precipitate and vacuum drying, aminated silica was obtained. A3: Spread aminated silica evenly in a quartz boat and place it in the constant temperature zone of a tube furnace. First, heat it to 450℃ under a nitrogen atmosphere and hold it for 30-40 minutes. Then, hold it for 30-40 minutes under a mixed atmosphere of hydrogen and nitrogen. Next, heat it to 650-700℃ and inject a ferrocene xylene solution into the vaporization zone at 220℃ at the front end of the quartz tube. At the same time, introduce acetylene and hold it for 30-40 minutes. Then, turn off the acetylene and injection pump and cool it to 100-200℃. Finally, cool it under a pure nitrogen atmosphere to obtain modified silica.

3. The lightweight recoating material for automobiles according to claim 2, characterized in that, The mass ratio of deionized water, polyacrylic acid aqueous solution, N,N'-methylenebisacrylamide, ammonium persulfate, hexadecyltrimethylammonium bromide, and tetraethyl orthosilicate in A1 is 200-250:100:0.5:0.1:2:20; The mass fraction of the polyacrylic acid aqueous solution described in A1 is 10%.

4. The lightweight recoating material for automobiles according to claim 2, characterized in that, The mass ratio of the porous hollow silica microspheres, ethanol, and 3-aminopropyltriethoxysilane described in A2 is 2:100-120:0.4-0.

8.

5. The lightweight recoating material for automobiles according to claim 2, characterized in that, The ratio of aminated silica to xylene solution of ferrocene described in A3 is 2g: 20-30mL; The concentration of the ferrocene xylene solution described in A3 is 0.05 g / mL; The acetylene flow rate described in A3 is 50 sccm.

6. The lightweight recoating material for automobiles according to claim 1, characterized in that, The modified titanium dioxide microspheres are prepared as follows: B1: Add nano-titanium dioxide to anhydrous ethanol and sonicate for 1-2 hours. Then add octadecylamine and citric acid and stir and reflux at 80°C for 6-12 hours. After centrifugation, washing the precipitate and vacuum drying, pretreated titanium dioxide is obtained. B2: Add pretreated titanium dioxide to dicyclopentadiene and sonicate for 30-50 min, then add toluene-2,4-diisocyanate, dibutyltin dilaurate, and tert-butyl peroxide and stir for 10-15 min to obtain a composite oil phase; B3: Add deionized water to polyvinyl alcohol 1788 aqueous solution and stir at 45℃ for 20-30 min. Then add composite oil phase and emulsify for 10-15 min. Then sonicate for 3-5 min. Then add ethylenediamine aqueous solution dropwise and stir for 6-7 h. After cooling, centrifuge, wash precipitate and freeze dry to obtain modified titanium dioxide microspheres.

7. The lightweight recoating material for automobiles according to claim 6, characterized in that, The mass ratio of anhydrous ethanol, nano-titanium dioxide, octadecylamine, and citric acid in B1 is 200-220:5:2.5:0.

1.

8. The lightweight recoating material for automobiles according to claim 6, characterized in that, The mass ratio of dicyclopentadiene, pretreated titanium dioxide, toluene-2,4-diisocyanate, dibutyltin dilaurate, and tert-butyl peroxide in B2 is 100:1.5:20:0.2:0.3-0.

4.

9. The lightweight recoating material for automobiles according to claim 6, characterized in that, The mass ratio of polyvinyl alcohol 1788 aqueous solution, deionized water, composite oil phase, and ethylenediamine aqueous solution in B3 is 300:100:121.7:25-28; The mass fraction of the polyvinyl alcohol 1788 aqueous solution described in B3 is 2%; The mass fraction of the ethylenediamine aqueous solution described in B3 is 20%.

10. A method for preparing a lightweight recoating material for automobiles according to any one of claims 1-9, characterized in that, Includes the following steps: Add polyvinyl chloride resin and diisononyl phthalate 1 to polyvinyl chloride paste resin and disperse for 8-10 min. Then add adhesion promoter and viscosity reducer and stir for 3-5 min. Then add calcium oxide, modified silica, zinc oxide, active nano calcium carbonate, heavy calcium carbonate and diisononyl phthalate 2 in sequence while stirring and stir for 45-50 min. Then add modified titanium dioxide microspheres and stir for 10-15 min. Then roll and grind to a fineness of 15-25 μm. Finally, transfer to a reaction vessel, evacuate, add foaming agent and disperse for 5-7 min. After vacuum standing at 70-80℃ for 24-30 h, a lightweight recoating material for automobiles is obtained. The mass ratio of diisononyl phthalate 1 to diisononyl phthalate 2 is 14-16:8-10.

Citation Information

Patent Citations

  • Weather-resistant glass cement

    CN109280525A

  • Automotive PVC stone chip resistant paint and preparation method thereof

    CN109749534A

  • High-temperature-resistant gel particle while-drilling plugging agent as well as preparation method and application thereof

    CN114426813A

  • Low-specific-gravity stone-chip-resistant coating for aluminum vehicle body as well as preparation method and application thereof

    CN115851047A

  • Micro-nano spherical modified silicon dioxide acid gelling agent, preparation method therefor, and use thereof

    WO2024007759A1